2023
DOI: 10.1039/d2nr07080d
|View full text |Cite
|
Sign up to set email alerts
|

Scalable and green formation of graphitic nanolayers produces highly conductive pyrolyzed paper toward sensitive electrochemical sensors

Abstract: While the pyrolyzed paper (PP) is a green and abundant material that can provide functionalized electrodes with wide detection win-dows for a plethora of targets, it poses long-standing challenges against...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 46 publications
0
7
0
Order By: Relevance
“…For the control sample (PP), it is observed that approximately 50% of the carbon is in sp 2 hybridization (∼284.3 eV). This result is indicative of the formation of π bonds that give rise to the high conductivity of PP . In addition, the presence of carbon with sp 3 -type hybridization (∼285.0 eV) was verified, referring to defect-like carbon.…”
Section: Resultsmentioning
confidence: 68%
See 4 more Smart Citations
“…For the control sample (PP), it is observed that approximately 50% of the carbon is in sp 2 hybridization (∼284.3 eV). This result is indicative of the formation of π bonds that give rise to the high conductivity of PP . In addition, the presence of carbon with sp 3 -type hybridization (∼285.0 eV) was verified, referring to defect-like carbon.…”
Section: Resultsmentioning
confidence: 68%
“…Thus, the changes observed in the morphology in Figure b for each treatment step barely affect the roughness of the electrodes. To study alterations in the carbonaceous structure, we monitored D, D2, D3, D4, and G bands in Raman spectra , for the thermally treated samples, shown in Figure b. The D band (∼1335 cm –1 ) is related to aromatic clusters with more than six (6) rings, while the D2 (∼1500 cm –1 ), D3 (∼1200 cm –1 ), and D4 (∼1620 cm –1 ) bands are attributed, respectively, to disordered graphene surface layers, functional groups, and small aromatic clusters and ethers.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations